Return to the Crystal Castle - Wurfel, Marlene (My University, 2021)
Another original story written by Marlene Wurfel especially for Tales from the Lilypad listeners everywhere. Return to the Crystal Castle with an ambitious princess for some adventure in the moonlight. Will Princess Dee succeed in a heroes quest? Intro music by Reid Alexander Whelton FairyTale Waltz by Kevin MacLeod is licensed under a Creative Commons Attribution 4.0 license. https://creativecommons.org/licenses/by/4.0/ Source: http://incompetech.com/music/royalty-free/index.html?isrc=USUAN1100232 Artist: http://incompetech.com/
Keywords: storytelling; children's stories